2017
DOI: 10.5902/2358198028147
|View full text |Cite
|
Sign up to set email alerts
|

Anatomia da madeira de Mimosa Balduinii Burkart

Abstract: 25 INTRODUÇÃOO gênero Mimosa L. compreende cerca de 530 binômios válidos, em sua grande maioria da região Neotropical, havendo 31 espécies na ilha de Madagascar e um número menor no leste da África e sudeste da Ásia (Coutinho, 2009 The wood anatomical structure of Mimosa balduinii is described, based on material collected in Rio Grande do Sul State, Brazil. In addition to short vascular elements, simple perforation plates, alternating and vestured vessel pits, paratracheal parenchyma and libriform fibers, that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…In that study, the authors observed that the species Tachigali poeppigiana, Tachigali setifera and Tachigali subvelutina showed solitary, twinned, triple or even quadruple pores, diffuse porosity and rays visible only with 10× approximation. These characteristics, according to Reis et al (2011), andMachado et al (2017), are common for species from the Fabaceae family, which generally have paratracheal parenchyma, few pores, short and libriform fibers.…”
Section: Discussionmentioning
confidence: 88%
“…In that study, the authors observed that the species Tachigali poeppigiana, Tachigali setifera and Tachigali subvelutina showed solitary, twinned, triple or even quadruple pores, diffuse porosity and rays visible only with 10× approximation. These characteristics, according to Reis et al (2011), andMachado et al (2017), are common for species from the Fabaceae family, which generally have paratracheal parenchyma, few pores, short and libriform fibers.…”
Section: Discussionmentioning
confidence: 88%